THE INFLUENCE OF THE RUPIAH EXCHANGE, INTEREST RATE, NET PROFIT MARGIN, PRICE EARNING RATIO, RETURN ON ASSET ON STOCK PRICE - Zakiyah, Dina; Istifadah, Nurul (ABDI EQUATOR, 2023)
The arrival of the capital market in Indonesia has provided many alternatives for investors to invest their excess funds and facilities for accelerating the acceleration of economic development in Indonesia. One of the securities contained in the stock is the industry's stock price that continues to change. In Indonesia, companies in the consumption sector are an industrial sector that is growing quite rapidly despite the unstable economic environment. Stocks in the consumption industrial zone can survive so that investors prefer to invest their funds in the consumer goods industrial sector. The study procedure used a multiple regression model. Information obtained through secondary sources. The result of this research is that Return on Assets partially affects stock prices. Simultaneously all variables affect stock prices.